Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick Untuk Meningkatkan Hasil Belajar Konsep Perpindahan Panas Pada Siswa Kelas V SD Inpres 48 Ambon: Indonesia - Izaack, Anaci Since; Rumahlatu, Dominggus; Talakua, Melvie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the application of the cooperative learning model of talking stick type in improving the learning outcomes of heat transfer concepts in grade V students of SD Inpres 48 Ambon. The type of research used is Classroom Action Research (PTK). Based on the data obtained during the implementation of cycles I and II, the research results in cycle I were still in the sufficient category (C) while for cycle II it increased to the very good category (SB). The conclusion in this study shows that student learning outcomes on the concept of heat transfer in grade V students of SD Inpres 48 Ambon by applying a cooperative learning model of talking stick type have increased.